Industri Halal Sebagai Solusi Peningkatan Pertumbuhan Ekonomi Di Nusa Tenggara Barat - Silalahi, Purnama Ramadani; Imsar, Imsar; Fattah, Abdul (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze the halal industry as a solution to increase economic growth in West Nusa Tenggara. The research approach uses a qualitative approach with in-depth interview methods. The findings in this research are that economic growth in a province can be increased, one of which is through optimizing the halal industry. By optimizing sharia-based industry, it will become an attractive brand for investors, tourists and creative economy players to improve the economy in NTB. This labeling of the halal industry must of course be supported by binding and sustainable provincial government regulations. So the existence of a halal park industry roadmap designed by the provincial government really helps accelerate the halal industry so that economic growth in NTB can grow and be strong. The halal industry not only pays attention to halal tourism, halal food, halal cosmetics and medicines but also pays attention to the facilities and infrastructure of the sharia financial industry, where the growth of sharia industrial assets in NTB is currently still relatively slow. The role of the OJK as well as financial and non-bank institutions is very much needed so that this halal industry can develop well.